2022
DOI: 10.1101/2022.11.22.517486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cation/H+exchanger OsCAX2 is involved in cadmium tolerance and accumulation through vacuolar sequestration in rice

Abstract: Excessive cadmium (Cd) in rice grains is a serious food safety problem. The development of Cd-safe varieties requires the identification of germplasms and genes with major effect on Cd accumulation but without negative effects on other important traits. Here, we reported that OsCAX2, a member of the rice Cation/H+ exchanger (CAX) family, is an important Cd transporter. OsCAX2 encodes a tonoplast-localized protein and is strongly upregulated by Cd, mainly expresses in root exodermis, parenchyma in cortex, endod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Under Cd stress, several metal transporter proteins participate in the absorption, transportation, and chelation of Cd by plants. These proteins include the Zn-regulated transporter/Fe-regulated transporter-like protein (ZIP) family, the cation exchanger (CAX) family, , the natural resistance-associated macrophage protein (NRAMP) family, the heavy-metal ATPase (HMA) family, the ATP-binding cassette (ABC) transporter family, and the yellow stripe-like transporter (YSL) family . These transmembrane transporters play a crucial role in regulating the distribution of metals within different compartments of plants.…”
Section: Resultsmentioning
confidence: 99%
“…Under Cd stress, several metal transporter proteins participate in the absorption, transportation, and chelation of Cd by plants. These proteins include the Zn-regulated transporter/Fe-regulated transporter-like protein (ZIP) family, the cation exchanger (CAX) family, , the natural resistance-associated macrophage protein (NRAMP) family, the heavy-metal ATPase (HMA) family, the ATP-binding cassette (ABC) transporter family, and the yellow stripe-like transporter (YSL) family . These transmembrane transporters play a crucial role in regulating the distribution of metals within different compartments of plants.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the rice OsCAXs family has six members, namely OsCAX1a, OsCAX1b, OsCAX1c, OsCAX2, OsCAX3 and OsCAX4 [132]. Among them, the loss of OsCAX2 function resulted in increasing Cd toxicity, while the upregulation of its expression significantly inhibited Cd accumulation in rice [133]. Preliminary evidence from a yeast heterologous system showed that OsCAX1a, OsCAX1c and OsCAX4 had Cd transport activity in rice [132].…”
Section: Calcium Carrier Proteins (Caxs) Familymentioning
confidence: 99%